Dual-release hydrocortisone treatment improves serum and peripheral blood mononuclear cell inflammatory and immune profiles in patients with autoimmune primary adrenal insufficiency - Tomasello, Laura; Coppola, Antonina; Pizzolanti, Giuseppe; Giordano, Carla; Arnaldi, Giorgio; Guarnotta, Valentina (Frontiers in Immunology, 2025)
ObjectiveThe primary outcome was the evaluation of the T-cell phenotype in autoimmune primary adrenal insufficiency (PAI). Secondary outcomes included the evaluation of the CD4+CD25+Foxp3+ Treg population and the gene expression levels of IL-6, IL-17A, cyclooxygenase (COX)-2, heat shock proteins (HSP)-70, indoleamine-2,3-dioxygenase (IDO), programmed death-ligand 1 (PD-L1), inducible nitric oxide synthase (iNOS), and thioredoxin (TXN)-1.MethodsWe prospectively included 15 patients with PAI on conventional glucocorticoid (GC) replacement therapy, 15 switched to dual-release hydrocortisone (DR-HC), and 20 healthy controls. Serum inflammatory parameters and peripheral blood mononuclear cells (PBMCs) were evaluated at baseline and after 12 months of treatment.ResultAt baseline, significantly higher CD4+ and CD8+ (both p < 0.001) T-cell percentages, a lower CD4+/CD8+ ratio (p < 0.05), and higher CD25+ and CD4+/CD25+ T cells (both p < 0.001) were observed in PAI compared to controls. After 12 months of DR-HC treatment, we found significantly lower IL-6 (p = 0.019), IL-17A (p = 0.046), COX-2 (p < 0.001), HSP-70 (p = 0.006), and TXN-1 (p = 0.008) and higher PD-L1 (p < 0.001) and IDO (p < 0.001) mRNA values compared to baseline. After 12 months of DR-HC treatment, a significant increase in CD4+ T cells (p = 0.012), PD-L1 (p = 0.003), and IDO (p < 0.001) and a decrease in CD8+ T cells (p < 0.001), IL-6 (p = 0.003), IL-17A (p = 0.0014), COX-2 (p < 0.001), HSP-70 (p = 0.005), and TXN-1 (p = 0.0008), as well as a significantly higher conversion in the CD4+/CD8+ ratio (p = 0.033), were observed compared to conventional GCs.ConclusionsThe switch from conventional GCs to DR-HC treatment altered the T lymphocyte phenotype and CD4+/CD8+ ratio in a Treg-independent manner, inducing significant improvements in the immune and inflammatory profile in PAI.